2019
DOI: 10.1111/1462-2920.14708
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell determination of iron content in magnetotactic bacteria: implications for the iron biogeochemical cycle

Abstract: Summary Magnetotactic bacteria (MTB) are ubiquitous aquatic microorganisms that mineralize dissolved iron into intracellular magnetic crystals. After cell death, these crystals are trapped into sediments that remove iron from the soluble pool. MTB may significantly impact the iron biogeochemical cycle, especially in the ocean where dissolved iron limits nitrogen fixation and primary productivity. A thorough assessment of their impact has been hampered by a lack of methodology to measure the amount of, and vari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 41 publications
6
46
0
Order By: Relevance
“…However, few studies have reported MTB in waterlogged soils [ 22 , 23 ]. Magnetosomal biogenesis by MTB is recognized as a key component of the global iron cycle [ 24 , 25 ], and MTB cells are potentially important in the biogeochemical cycling of carbon, phosphorus, nitrogen, and sulphur [ 9 , 26 – 28 ]. Historically, magnetosomal biomineralization has been viewed as a specialized type of metabolism restricted to two Bacterial phyla: the Proteobacteria ( Alphaproteobacteria , Deltaproteobacteria , and Gammaproteobacteria classes) and the Nitrospirae [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have reported MTB in waterlogged soils [ 22 , 23 ]. Magnetosomal biogenesis by MTB is recognized as a key component of the global iron cycle [ 24 , 25 ], and MTB cells are potentially important in the biogeochemical cycling of carbon, phosphorus, nitrogen, and sulphur [ 9 , 26 – 28 ]. Historically, magnetosomal biomineralization has been viewed as a specialized type of metabolism restricted to two Bacterial phyla: the Proteobacteria ( Alphaproteobacteria , Deltaproteobacteria , and Gammaproteobacteria classes) and the Nitrospirae [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of biomineralization of magnetite or greigite, MTB take up large amounts of dissolved iron from the surrounding environment and sequester it in magnetosomes as iron crystals. As such, the role that MTB play in iron cycling in both freshwater bodies and the ocean is potentially quite large [5,8]. Conservative estimates from Amor and colleagues indicate that estuarine and oceanic MTB may take up anywhere from approximately 1% to 50% of dissolved iron inputs (approximately 9 × 10 8 kg per year) in their environments [8].…”
Section: Introductionmentioning
confidence: 99%
“…As such, the role that MTB play in iron cycling in both freshwater bodies and the ocean is potentially quite large [5,8]. Conservative estimates from Amor and colleagues indicate that estuarine and oceanic MTB may take up anywhere from approximately 1% to 50% of dissolved iron inputs (approximately 9 × 10 8 kg per year) in their environments [8]. Having a greater understanding of the iron regulation strategies encoded within the genomes of MTB, as well as how iron is taken up and distributed to magnetosomes, is important for a more accurate picture of the role of MTB in their aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, spICP‐MS can provide the elemental compositions of hundreds to thousands of suspended nanoparticle aggregates within minutes (Lee et al ., 2014; Bevers et al, 2020). A derivation of this technique has already been used to probe the variation in Fe content of magnetotactic bacteria at the single cell levels using single‐cell ICP‐MS (Amor et al ., 2020). All of these techniques will be capable of probing microbe‐nanoparticle interactions at an unprecedented scale.…”
Section: Future Directionsmentioning
confidence: 99%